BIOEKOLOGI IKAN MANGGABAI (Gloss BIOEKOLOGI IKAN MANGGABAI (Glossogobius giuris) DI DANAU LIMBOTO - Dewi Nuryanti Fazrin; Hasim Hasim; Juliana Juliana (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
The purpose of this study was to determine the relationship between the length and weight of Manggabai fish (Glossogobius giuris) and to know the relationship between the presence of Manggabai fish (Glossogobius giuris) and water quality in Limboto Lake. This research was conducted in February 2019, located in the waters of Lake Limboto, Gorontalo Province. The method used in determining the location of sampling is Purposive Sampling. Fish sampling is determined by considering fishing locations, litoral areas, the presence of residential areas, agricultural and plantation areas, the existence of floating net cages and in the middle of the lake. The study was conducted at 20 observation stations using fish traps in the form of bamboo and used motorcycle tires that have been modified and become traditional fishing gear. The results showed that the physical and chemical parameters in Lake Limboto and showed temperature values ​​ranged from 29.77 to 31.630C, dissolved oxygen levels ranged from 2.1 to 5.48 ppm, pH ranged from 7.09 to 8.94, TDS ranging from 0.251 to 0.369, Nitrite Levels 0.04-0.08 ppm, Nitrate Levels 1.2-4.7 ppm, BOD ranges from 2.5-57 ppm and phosphate levels 0.1-1.14 ppm. The relationship between length and body weight of fish are allometric, where W = 0.8769 L10,023 and constant b (10,023)> 3.